Islamic Higher Education in the Perspective of Imre Lakatos' Research Program Method - M. Nuzulul Ulum; Amri Saputra; Nur Fadilah Ramadhany (Yayasan Zia Salsabila, 2026)
This study aims to analyze Islamic higher education through the perspective of the Methodology of Scientific Research Programmes developed by Imre Lakatos. This approach is employed to understand how the epistemological structure of Islamic education can be developed progressively without losing the revelatory values as its fundamental core. The study adopts a qualitative method with a library research design, in which data are collected from various literature sources such as books, journals, and relevant scholarly works. The findings indicate that the application of the concepts of hard core, protective belt, and a series of theories within Islamic higher education can serve as a methodological framework that maintains a balance between the Islamic intellectual tradition and modern scientific innovation. Through Lakatos’s approach, Islamic higher education is expected to develop research that is progressive, rational, and grounded in spiritual values, thereby enabling it to respond to the challenges of globalization and digitalization without losing its epistemological identity. Accordingly, Lakatos’s research programme methodology has the potential to become a new paradigm in the development of Islamic epistemology that is dynamic, adaptive, and sustainable.